Liofilização de frutas tropicais - Marques, Luanda Gimeno (2008)
The national and international markets of processed fruits have continually grown due to the improved quality of the marketed product, the convenience of ready-to-serve products and because the availability of seasonal commodities has been extended by the processing which acts as a preservation technique. Besides aggregating commercial value to the fruit, drying reduces the wastes and the posharvest losses. Freezing-drying is the best drying method for heat sensitive materials and for obtaining a high quality dried product. Consequently, it has mainly been employed in the dehydration of materials with high commercial value such as tropical fruits. In order to contribute with the studies on lyophilization, the objective of this research was to analyse the freeze-drying of five tropical fruits, namely pineapple, acerola, guava, papaya and mango. For this, specific studies were carried out involving the determination of both the freezing and sublimation fronts, the analysis of the freeze-drying kinetics, the determination of structural properties (true and apparent densities and porosity) as a function of moisture content as well as of thermal properties (specific heat, thermal diffusivity and thermal conductivity) of the freeze-dried and fresh fruits. The influence of the process on the product quality was also evaluated through the determination of glass transition temperature, the vitamin C, total carotenoids, calcium and phosphorus contents and rehydration characteristics of the freeze-dried fruits. Total content of carotenoids was related to the values of chromatic parameters (L*, a*, and b*). Sorption isotherms of freeze-dried acerola using three freezing techniques (freezer, liquid nitrogen and nitrogen vapor) were determined. Empirical e semi-empirical equations were evaluated to describe to describe freeze-drying and rehydration kinetics. From indices that take into account the quantity of water absorbed and the losses of solutes it was possible to fully characterize the rehydration process of the freeze-dried fruits. Their water uptake capacity was affected not only by injuries during moisture removal but also by structural collapse induced by the rehydration process itself, which was explained using the glass transition concept. The shrinkage magnitude and the thermal behaviour of freeze-dried fruits were also affected by the glass transition phenomenon. Finally, freeze-drying and convective drying were compared in terms of product quality attributes, such as shrinkage, vitamin C retention and rehydration characteristics. Freeze-dried fruits were characterized by highly porous structures, high water uptake rates and elevated preservation of nutrients. The improved quality of the product is one of the main reasons that can contribute for increasing the demand for freeze-dried fruits in the food industry.